Konstitusi dan Hukum Perundang-Undangan - Kurnia, Kamal Fahmi; Aliansa, Yoga; Agustian, Zulpa (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The constitution and statutory law are two important pillars in running a country's legal system. The constitution is the highest legal basis that determines the structure of government, the rights of citizens, and the mechanism for exercising power. On the other hand, statutory law is the entirety of the legal regulations produced by the legislature and functions to regulate people's lives and provide a framework for decision-making and dispute resolution. This research explores the important role of the constitution and statutory law in ensuring justice, stability, and security of a country and how the two interact to achieve these goals. Keywords: Constitution, statutory law, legal system, government, citizens' rights, legislature, justice, stability, security, interaction.